Overexpression of miR-21-5p promotes proliferation and invasion of colon adenocarcinoma cells through targeting CHL1 - Weihua Yu; Kongxi Zhu; Yulong Wang; Hualong Yu; Jianqiang Guo (BMC, 2018)
Abstract Background This study aims to investigate the effect of miR-21-5p on process of colon adenocarcinoma (COAD) cells and its connection with neural cell adhesion molecule L1 (CHL1). Methods Different expressions of mRNAs and miRNAs were calculated with microarray analysis. QRT-PCR and western blot were performed to quantify miR-21-5p and CHL1 expression. Flow Cytometry, MTT assay, colony formation assay, transwell assay and ELISA were performed to evaluate propagation and invasiveness of COAD cells. Dual luciferase reporter assay was employed to scrutinize the relationship between miR-21-5P and CHL1. We performed in vivo experiment to detect the impact of miR-21-5p and CHL1 on COAD tumor growth. Results Expression level of miR-21-5p increased in both COAD tissues and cells. MTT and Cell cycle assay showed that overexpression of miR-21-5p accelerated proliferation of COAD cells. Transwell assay indicated that miR-21-5p promoted cell invasion. The result of dual luciferase reporter assay indicated that miR-21-5p targeted CHL1 directly and inhibited its expression. The result of in vivo experiments showed that down-regulation of miR-21-5p decreased the volume and weight of tumor, while knockdown of CHLI stimulated tumor growth. Conclusions The overexpression of miR-21-5p can promote propagation and invasiveness of COAD cells through inhibiting the expression of CHL1.